THE EFFECT OF INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) ADOPTION ON THE QUALITY OF ACCOUNTING INFORMATION IN MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE 2017 – 2020 - Adelia Ika Prasetyawati; Sri Wiranti Setiyanti; Arini Novandalina (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
ABSTRACT The implementation of IFRS-based accounting standards emphasizes more informative financial report disclosure which will improve the quality of the company's financial reports. Improving the quality of financial reports is demonstrated by increasing the quality of the accounting information reported. The quality of accounting information in this research uses the value relevance of information and the reliability of accounting information. The aim of this research is to test whether IFRS has an effect on the value relevance of accounting information and the reliability of accounting information in manufacturing companies. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2020 period. There are 164 manufacturing companies registered on the IDX. The sampling technique in this research used a purposive sampling method. There were 25 companies that met the sample criteria so that the total observations were 100 company data. The variable in this research is the quality of accounting information which is proxied by relevance and reliability as the dependent variable, and the independent variable is the adoption of International Financial Reporting Standards (IFRS). The IFRS adoption variable in this research uses a dummy variable. Data collection was carried out by observing the financial report data of manufacturing companies listed on the Indonesia Stock Exchange 2017-2020. Data analysis was carried out using classic assumption tests and hypothesis testing using simple linear regression. The results of the relevance test on IFRS adoption show that the significance value of the hypothesis test on the relevance of the IFRS adoption value is 0.046. It can be concluded that the relevance of the profit value has a positive influence, while on the reliability of the IFRS adoption value it is 032, which means that the value reliability has a positive influence. Then the coefficient of determination test value or R Square Relevance is 0.339, which means that 33.9% of the relevance of the information value is influenced by IFRS adoption, and the value of the coefficient of determination or R Square Reliability is 0.331, which means that 33.1% of the reliability of the information value is influenced by adoption. So it can be concluded that the relevance of the value of accounting information and the reliability of the value of information on IFRS adoption are full and have a positive influence. For further research, it is recommended to add a longer research period with the latest year so that more samples are taken, consider adding research variables so that the composition of the quality of accounting information is more complete and detailed. Keywords: IFRS, Relevance, Reliability, Quality of Accounting Information Value, Information Value